PENDAMPINGAN PENCATATAN KEUANGAN SEDERHANA UMKM BERBASIS MICROSOFT EXCEL - Anggita, Delia; Nursya'bani, Anisa; Nopiyanti, Farida; Hafizah, Nadia Zalfa; Tamyiz, Nazhwa Nayla Putri; Hidayat, Sabilla Dwi Lestari; Mediawati, Elis (Universitas Mataram, 2025)
Financial recording and reporting are essential components to support business sustainability, including in the Micro, Small, and Medium Enterprises (MSMEs) sector. However, many MSMEs still lack understanding of the importance of systematic financial recording, resulting in difficulties in monitoring business performance and growth. This situation is worsened by the limited use of digital technology, leading to low utilization of financial recording software for effective and accountable financial management. To address this issue, efforts were made to improve MSME understanding and skills in digital financial recording using Microsoft Excel to produce more systematic financial reports. The community service activities were carried out through participatory mentoring methods, including initial observation, preparation, mentoring implementation, and evaluation. Mentoring was conducted through training sessions using Microsoft Excel for systematic financial recording, accompanied by Question-and-Answer discussions. The evaluation results showed that the provided Excel template was well-received by the partner. It facilitated systematic recording, classification, and recapitulation of financial transactions. However, full implementation could not be realized immediately as the partner needed time to understand and practice using the template features. The partner plans to implement it in the upcoming academic period. Although full implementation has not yet occurred, the partner showed a positive commitment to learning further. The mentoring team plans to continue supporting the partner to ensure smoother implementation in the future. This activity successfully provided a solution to the partner’s financial recording problems through the Excel-based template, with a visible positive impact on understanding and awareness improvement.